Moonlight on the millpond ebook - Wick, Lori (Tucker Mills Trilogy, 2005)
This first book in the Tucker Mills Trilogy from beloved author Lori Wick follows Jace Randall as he leaves his childhood home to help his Uncle Woody Randall run the saw mill in Token Creek. Jace diligently focuses on work until he meets the visiting niece of local storekeepers. Jace pursues her until she finally agrees to attend a picnic with him and take a chance. But before the relationship has a strong foundation, the couple separates because of gossip fueled by Jace's sister. Later, when she admits her wrongdoing and shares her testimony of a new faith, the couple must decide whether to try again. Will the sister's example of faith and transformation be enough to restore broken dreams?